Enhancement of synchronized activity between hippocampal CA1 neurons during initial storage of associative fear memory. (30th June 2017) - Liu, Yu‐Zhang; Wang, Yao; Shen, Weida; Wang, Zhiru
Abstract : Key points: Learning and memory storage requires neuronal plasticity induced in the hippocampus and other related brain areas, and this process is thought to rely on synchronized activity in neural networks. We used paired whole‐cell recording in vivo to examine the synchronized activity that was induced in hippocampal CA1 neurons by associative fear learning. We found that both membrane potential synchronization and spike synchronization of CA1 neurons could be transiently enhanced after task learning, as observed on day 1 but not day 5. On day 1 after learning, CA1 neurons showed a decrease in firing threshold and rise times of suprathreshold membrane potential changes as well as an increase in spontaneous firing rates, possibly contributing to the enhancement of spike synchronization. The transient enhancement of CA1 neuronal synchronization may play important roles in the induction of neuronal plasticity for initial storage and consolidation of associative memory. Abstract: The hippocampus is critical for memory acquisition and consolidation. This function requires activity‐ and experience‐induced neuronal plasticity. It is known that neuronal plasticity is largely dependent on synchronized activity. As has been well characterized, repetitive correlated activity of presynaptic and postsynaptic neurons can lead to long‐term modifications at their synapses. Studies on network activity have also suggested that memory processing in the hippocampus may involve learning‐induced changes of neuronal synchronization, as observed in vivo between hippocampal CA3 and CA1 networks as well as between the rhinal cortex and the hippocampus. However, further investigation of learning‐induced synchronized activity in the hippocampus is needed for a full understanding of hippocampal memory processing. In this study, by performing paired whole‐cell recording in vivo on CA1 pyramidal cells (PCs) in anaesthetized adult rats, we examined CA1 neuronal synchronization before and after associative fear learning. We first found in naive animals that there was a low level of membrane potential (MP) synchronization and spike synchronization of CA1 PCs. In conditioned animals, we found a significant enhancement of both MP synchronization and spike synchronization, as observed on day 1 after learning, and this enhancement was transient and not observed on day 5. Accompanying learning‐induced synchronized activity was a decreased firing threshold and rise time of suprathreshold MP changes as well as an increased spontaneous firing rate, possibly contributing to the enhanced spike synchronization. The transiently enhanced CA1 neuronal synchronization may have important roles in generating neuronal plasticity for hippocampal storage and consolidation of associative memory traces. Key points: Learning and memory storage requires neuronal plasticity induced in the hippocampus and other related brain areas, and this process is thought to rely on synchronized activity in neural networks. We used paired whole‐cell recording in vivo to examine the synchronized activity that was induced in hippocampal CA1 neurons by associative fear learning. We found that both membrane potential synchronization and spike synchronization of CA1 neurons could be transiently enhanced after task learning, as observed on day 1 but not day 5. On day 1 after learning, CA1 neurons showed a decrease in firing threshold and rise times of suprathreshold membrane potential changes as well as an increase in spontaneous firing rates, possibly contributing to the enhancement of spike synchronization. The transient enhancement of CA1 neuronal synchronization may play important roles in the induction of neuronal plasticity for initial storage and consolidation of associative memory.